20-years experiens of pulmonary autograft operation - Romanyuk, O. M.; Klymyshyn, Y. I.; Rudenko, N. N.; Dovgan, A. M.; Yemets, I. M. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The paper presents results of the operation of aortic valve replacement by the own pulmonary valve – the pulmonary autograft operation in patients with aortic valve disease and the modifications of the surgical technique. Purpose: to analyze the twenty years of the pulmonary autograft procedure, to determine the causes of autograft dysfunction in follow-up period, to evaluate the effect of the autograft root reinforcement concept strengthening at two levels of the aortic root on the results of the operation. Method and material. 200 consecutive patients of different age groups, which performed a pulmonary autograft operation for the period from 1996 to 2017. In 127 patients, our own surgical modifications (autograft root reinforcement) were used to strengthen the root of an autograft and to form a new pulmonary artery. Results. Survival was 95.3%, 92.1% and 92.1% during 1, 10 and 15 years of follow-up. The risk factors for mortality were: the age of patients under 1 year, the increase of the ischemic time and bypass, significantly reduced the risk with the use of surgical modifications. Echocardiographic results: minimal neoaortic insufficiency was observed in 130 (76%) moderate – in 25 patients (15%), in 10 (6%) patients – moderate-to-severe and severe – in 5 (3%) patients. Risk factors for autograft dysfunction were: older age of patients, NYHA functional class, duration of operation; use of surgical modifications reduced this risk. Conclusion. The use of a pulmonary valve as an aortic prosthesis provides growth of the neo-aortic root, a low incidence of aortic valve dysfunction, and a low frequency of reoperations. The use of own modifications of the operation showed effectiveness, greatly improving the immediate and long-term results.